2011
DOI: 10.3399/bjgp11x572454
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular multimorbidity: the effect of ethnicity on prevalence and risk factor management

Abstract: BackgroundMultimorbidity is common in primary care populations. Within cardiovascular disease, important differences in disease prevalence and risk factor management by ethnicity are recognised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 68 publications
(119 citation statements)
references
References 29 publications
(37 reference statements)
5
110
0
4
Order By: Relevance
“…Similar to other studies, older age (77-78% of this cohort 65+ years old) showed the highest odds of medical comorbidity. 8,14,27 However, among those with at least 50% service-connected disability, the highest odds of comorbidity type were driven by mental health.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar to other studies, older age (77-78% of this cohort 65+ years old) showed the highest odds of medical comorbidity. 8,14,27 However, among those with at least 50% service-connected disability, the highest odds of comorbidity type were driven by mental health.…”
Section: Discussionmentioning
confidence: 99%
“…The significantly lower multimorbidity among married veterans resonates with other studies showing this finding as an important support mechanism for male versus female veterans. 31 Prior studies of racial/ethnic, regional, and rural/urban differences in diabetes outcomes [14][15][16][17][18] demonstrated a twofold higher potential for physical multimorbidity in non-Hispanic black patients due to poorer control of CVD risk factors and a lower rate of medication adherence. This study found that non-Hispanic black patients had 25-67% greater risk of medical, mental health, and combined comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Management of DM is also significantly worse, while management of high BP and hypercholesterolaemia is better among South Asians than host country natives. 220 The higher CVD risk among South…”
Section: Obstetric Conditionsmentioning
confidence: 99%